2022
DOI: 10.1093/hmg/ddac050
|View full text |Cite
|
Sign up to set email alerts
|

Multi-ancestry genome-wide association study of gestational diabetes mellitus highlights genetic links with type 2 diabetes

Abstract: Gestational diabetes mellitus (GDM) is associated with increased risk of pregnancy complications and adverse perinatal outcomes. GDM often reoccurs and is associated with increased risk of subsequent diagnosis of type 2 diabetes (T2D). To improve our understanding of the aetiological factors and molecular processes driving the occurrence of GDM, including the extent to which these overlap with T2D pathophysiology, the GENetics of Diabetes In Pregnancy (GenDIP) Consortium assembled genome-wide association studi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
66
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 69 publications
7
66
0
3
Order By: Relevance
“…T2D is characterized by persistently high blood glucose levels due to impaired insulin secretion from pancreatic β cells, insensitivity to insulin in peripheral tissues, and increased glucose production in the liver 107 . Several well-established genetic risk factors for T2D are variants in the transcription factor 7-like 2 (TCF7L2) gene 108-110 that drive expression of functional splice isoforms of this gene 109,111 . The protein product of this gene is the high mobility group box-containing transcription factor TCF7L2 which activates Wnt signaling with tissue-specific outcomes 108,112-114 .…”
Section: Discussionmentioning
confidence: 99%
“…T2D is characterized by persistently high blood glucose levels due to impaired insulin secretion from pancreatic β cells, insensitivity to insulin in peripheral tissues, and increased glucose production in the liver 107 . Several well-established genetic risk factors for T2D are variants in the transcription factor 7-like 2 (TCF7L2) gene 108-110 that drive expression of functional splice isoforms of this gene 109,111 . The protein product of this gene is the high mobility group box-containing transcription factor TCF7L2 which activates Wnt signaling with tissue-specific outcomes 108,112-114 .…”
Section: Discussionmentioning
confidence: 99%
“…Third, we acknowledged the lack of power in the GWAS database of GDM. Compared with the current GWAS database of GDM ( Pervjakova et al, 2022 ), the GDM database we collected only included 2062 GDM women, which might influence the statistical power of our MR results as we just extracted only two independent SNPs of GDM. We hope to include more GWAS studies with this complications in the future.…”
Section: Discussionmentioning
confidence: 99%
“…36 Other observational studies using multivariable regression have reported that maternal BMI is associated with higher risk of stillbirths 37 , induction 38 , caesarean section 38 , and not initiating breastfeeding. 39 Previous Mendelian randomization studies have focused on a limited set of outcomes and are supportive of higher maternal BMI being related to higher mean offspring birthweight 4,40,41 (N ∼ 9,000 to 400,000) and GDM 42 (N = 5,485 cases and 347,856 controls).…”
Section: Discussionmentioning
confidence: 99%